A Thematic Exegesis of The Qur’an on the Climate Crisis: An Analytical Study of Seyyed Hossein Nasr’s Ecological Philosophy - M. Nur Kholis Setiawan; Enjen Zaenal Mutaqin (Al-Bayan: Jurnal Studi Ilmu Al- Qur’an dan Tafsir, 2025)
The global climate crisis poses a serious threat to human sustainability that cannot be solved by technology alone. This article explores how thematic interpretation (tafsīr mawḍūʿī) of the Qur’an can help raise ecological awareness and responsibility, focusing on the environmental philosophy of Seyyed Hossein Nasr. Using a qualitative descriptive approach based on library research, the study analyses selected Qur’anic verses related to environmental ethics. It also reviews Nasr’s critique of modernity and his call to re-sacralise nature. The findings show that the Qur’an encourages environmental stewardship and ethical responsibility, while Nasr’s spiritual cosmology provides a strong theological basis for an ecological ethic grounded in the Qur’an. The study concludes that combining thematic Qur’anic interpretation with Nasr’s insights offers a comprehensive framework for addressing the climate crisis within Islamic thought. Additionally, institutional support, academic traditions, and digital platforms are essential to effectively promote these ecological values in contemporary Muslim communities.